A Survey on Customer Fulfillment with HDFC ATM in Kanchipuram District - Dr. M. R. Prakash; Mrs. G. Madhuri (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2022)
The impact of innovation over item developments in banks is gigantic. HDFC Bank is the biggest private segment banks. This study goes for dissecting the fulfillment levels of the clients of HDFC Bank holding ATM cards in Kanchipuram area concerning a few perspectives, for example, the administration nature of ATM work force, area, adequate number of ATMs in the area, normality in working of ATMs, their effect on general execution and their conclusions on different other related issues. 120 clients were chosen on arbitrary premise. Mean levels of fulfillment of the respondents were computed utilizing SPSS. The clients are profoundly fulfilled by the accessibility of trade out the ATMs and the nature of cash notes in the ATMs being positioned first and second.